Bee-Parasitic Strepsipterans (Strepsiptera: Stylopidae) Induce Their Hosts' Flower-Visiting Behavior Change. Issue 5 (3rd September 2021) - Nakase, Yuta; Kato, Makoto
Abstract: Parasites sometimes manipulate their host's behavior to increase their own fitness by enhancing the likelihood that their offspring will reach their hosts. Bees are often parasitized by immobile adult female strepsipterans which seem to modify bees' behavior to facilitate the release of mobile first-instar larvae onto flowers. To better understand how the parasite may modify the host's behavior, we compared the foraging behavior of the sweat bee Lasioglossum apristum (Vachal, 1903) (Hymenoptera: Halictidae) between bees parasitized and unparasitized by the strepsipteran Halictoxenos borealis Kifune, 1982 (Strepsiptera: Stylopidae). Both parasitized and unparasitized bees frequently visited Hydrangea serrata (Thunb.) (Cornales: Hydrangeaceae) inflorescences, which are polleniferous but nectarless. On H. serrata inflorescences, unparasitized bees collected pollen from the anthers, but parasitized bees did not collect or eat pollen. Instead, they displayed a peculiar behavior, bending their abdomens downward and pressing them against the flower. This peculiar behavior, which was observed only in bees parasitized by a female strepsipteran in the larvae-releasing stage, may promote the release of mobile first-instar larvae onto flowers. Our observations suggest that the altered flower-visiting behavior of parasitized bees may benefit the parasite. Moreover, it suggests that strepsipteran parasites may modify their host's behavior only when the larvae reach a certain life stage.